2015
DOI: 10.20950/1678-2305.2015v41nep707
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of animal protein sources by soy protein concentrate for juvenile Nile tilapia

Abstract: Soy protein concentrate (SPC) was evaluated as a dietary replacement of animal protein sources (fish meal and poultry by-product meal) (APS) for juvenile Nile tilapia (Oreochromis niloticus). Apparent digestibility coefficients (ADC) of crude protein (CP) and dry matter (DM) were evaluated by feeding tilapia an experimental diet composed of 69.5% reference diet, 30% SPC, and 0.5% chromic oxide as inert marker. Apparent digestibility coefficients were 96.57% for CP and 76.84% for DM. In a feeding trial, increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…SPC is an alternative protein source for aquaculture diets resulting from the alcoholic extraction of carbohydrates and some antinutritional factors from soybean meal. Although the SPC protein content (around 650 g/kg) is similar to FM, they are deficient in methionine (do Espirito Santo, Fernandes, & da Silva, 2015; Espe, Hevrøy, Liaset, Lemme, & El‐Mowafi, 2008; S. Kaushik et al, 1995; Riche & Williams, 2011; Storebakken, Shearer, & Roem, 2000). In this study, the diet with the complete replacement of FM by SPC was shown to be deficient in methionine, which agrees with previous studies on rainbow trout (S. Kaushik, Coves, Dutto, & Blanc, 2004), red sea bream, Pagrus major (Takagi et al, 2001), sole (Aragao et al, 2003), and Nile tilapia (do Espirito Santo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SPC is an alternative protein source for aquaculture diets resulting from the alcoholic extraction of carbohydrates and some antinutritional factors from soybean meal. Although the SPC protein content (around 650 g/kg) is similar to FM, they are deficient in methionine (do Espirito Santo, Fernandes, & da Silva, 2015; Espe, Hevrøy, Liaset, Lemme, & El‐Mowafi, 2008; S. Kaushik et al, 1995; Riche & Williams, 2011; Storebakken, Shearer, & Roem, 2000). In this study, the diet with the complete replacement of FM by SPC was shown to be deficient in methionine, which agrees with previous studies on rainbow trout (S. Kaushik, Coves, Dutto, & Blanc, 2004), red sea bream, Pagrus major (Takagi et al, 2001), sole (Aragao et al, 2003), and Nile tilapia (do Espirito Santo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although the SPC protein content (around 650 g/kg) is similar to FM, they are deficient in methionine (do Espirito Santo, Fernandes, & da Silva, 2015; Espe, Hevrøy, Liaset, Lemme, & El‐Mowafi, 2008; S. Kaushik et al, 1995; Riche & Williams, 2011; Storebakken, Shearer, & Roem, 2000). In this study, the diet with the complete replacement of FM by SPC was shown to be deficient in methionine, which agrees with previous studies on rainbow trout (S. Kaushik, Coves, Dutto, & Blanc, 2004), red sea bream, Pagrus major (Takagi et al, 2001), sole (Aragao et al, 2003), and Nile tilapia (do Espirito Santo et al, 2015). Generally, the supplementation of soy protein‐based diets with CAA resulted in growth performances comparable to FM‐based diets in different fish species (Boonyoung, Haga, & Satoh, 2013; Hernández, Martínez, Jover, & García, 2007; Li et al, 2015; Takagi et al, 2001; Venou, Alexis, Fountoulaki, & Haralabous, 2006; Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%